Bread or games?: A social cost-benefit analysis of the World Cup bid of the Netherlands and the winning Russian bid - de Nooij, M.; van den Berg, M.; Koopmans, C. (Journal of Sports Economics, 2013)
Many countries compete fiercely for the right to host mega-events like the World Cup. Proponents of hosting mega-events claim that yields economic gains. Many available studies focus on partial effects of hosting or concern ex post analyses. The authors utilize the existing literature to perform a detailed cost-benefit analysis (CBA) of the Netherlands bidding jointly with Belgium for the 2018 World Cup. The authors show that national pride and pleasure come at a price and financial gains are unlikely. Based on this CBA, the authors predict that the costs of the 2018 World Cup in Russia will also exceed the financial benefits.